Linguistic Capital and Development Capital in a Network of Cultural Producers: Mutually Valuing Peer Groups in the 'Interactive Fiction' Retrogaming Scene. (June 2016) - Allington, Daniel
This article reports on a mixed-methods study of the cultural valuing of 'interactive fiction' or 'text adventure games': a formerly commercial videogame genre sometimes associated with electronic literature but here argued to be best understood in context of the under-researched phenomenon of 'retrogaming' or 'old school gaming'. It is argued that a model for the study of retrogaming scenes is provided in Lena and Peterson's account of 'traditionalist' musical genres, and that these in turn exhibit similarities with Bourdieu's 'field of restricted production'. On the basis of qualitative analysis of interviews and documents and quantitative analysis of valuing behaviour on a website used by the interactive fiction community, it is proposed that entrance into the mutually-valuing peer group of interactive fiction developers is facilitated by possession of two intangible resources: linguistic capital (in the form of proficiency in Standard English) and development capital (in the form of expertise with programming languages specific to the production of interactive fiction), where development capital is a new concept that may be extensible to other technically-oriented digital cultures (for example, the working cultures of professional software developers and the communities that form around open source projects). Expressions of value in the form of star ratings were collected procedurally through data scraping, and represented as a directed graph. Seidman's k -core was innovatively used as an instrument for detecting mutually-valuing peer groups within that graph. It is argued that this methodology has general application for the study of cultural value and its production within social networks (both online and off), including networks associated with more established cultural fields such as art and literature.